Customers’ Continuance Intention in Using a Mobile Navigation App in the Tourism Context: What Factors Will Lead? - Allan, Mamoon (Academica Turistica - Tourism and Innovation Journal, 2022)
A mobile navigation app with a geographical information system is favoured to search addresses and find the fastest ways to reach a destination. However, there is a lack of scholarly attention to consumer behaviour and mobile navigation apps. This study aims to measure the impact of perceived enjoyment, perceived usefulness, customer satisfaction, and customer habit on continuance intention to use a mobile navigation app. Data were collected using an electronic survey; participants were approached by applying a convenient sampling method. According to Burns and Grove (2005, p. 351), ‘Convenience sampling is useful for descriptive and correlation studies conducted in new areas of research.’ In total, 212 participants were involved in this study, consisting of 110 females and 102 males. This study found that Google Maps and Waze were the most popular apps used by participants. Perceived enjoyment had a significant impact on perceived usefulness and habit. Perceived usefulness had a substantial effect on satisfaction. Satisfaction significantly influenced continuance intention. In addition, customer habit significantly affected satisfaction and continuance intention. This study discusses recommendations for future research. Keywords: continuance intention, customer habit, geographical information system (gis), Google Maps, mobile navigation application, technology adoption, tourism, Waze